Penerapan Model Pembelajaran Project Based Learning (PjBL) Berbantu Jobsheet untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Informatika - Anjjani Mardhika Adif; Lika Jafnihirda (SAFE-Network, 2025)
This study aims to improve student learning outcomes using the Project Based Learning learning model assisted by jobsheets in the Informatics subject of class X hospitality 6 at SMK Negeri 9 Padang in the 2024/2025 Academic Year. This study uses a classroom action research method (classroom action research), using cycle I and Cycle II consisting of planning, implementation of actions, observation, and reflection. The research subjects were 36 students of class X hospitality 6. The results of the study showed that the Percentage of Completeness of the learning outcomes of class X hospitality 6 students in Cycle I was 78% and in Cycle II was 92% and the grades obtained by students in the Informatics subject through the use of the Project Based Learning learning model assisted by jobsheets increased from cycle I to cycle II by 14%. The conclusion of this study is that Informatics learning carried out using the Project Based Learning learning model assisted by Jobsheets can have a very significant influence on improving the learning outcomes of class X hospitality 6 students at SMK Negeri 9 Padang with the percentage of learning completeness in cycle I and cycle II.